2006
DOI: 10.1007/s11302-006-9041-z
|View full text |Cite
|
Sign up to set email alerts
|

Shaping immune responses through the activation of dendritic cells’ P2 receptors

Abstract: Dendritic cells (DCs) activate and shape the adaptive immune response by capturing antigens, migrating to peripheral lymphoid organs where naïve T cells reside, expressing high levels of MHC and costimulatory molecules and by secreting cytokines and chemokines. DCs are endowed with a high degree of functional plasticity and their functions are tightly regulated. Besides initiating adaptive immune responses, DCs play a key role in maintaining peripheral tolerance toward self-antigens. On the basis of the inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 95 publications
0
1
0
Order By: Relevance
“…80 These effects are mimicked by the nonhydrolyzable ATP analog ATP-␥-S (an agonist of P2Y11) and by several cAMP-elevating agents, as well as by the administration of cell-permeable cAMP analogs. [80][81][82] Schnurr et al reported that P2Y11 activity inhibits IL-27 production. 83 In the same article, the authors reported the capacity of eATP to increase mRNA levels of IL-23, which potentially fosters the expansion of the proinflammatory Th17 lymphocyte subset.…”
mentioning
confidence: 99%
“…80 These effects are mimicked by the nonhydrolyzable ATP analog ATP-␥-S (an agonist of P2Y11) and by several cAMP-elevating agents, as well as by the administration of cell-permeable cAMP analogs. [80][81][82] Schnurr et al reported that P2Y11 activity inhibits IL-27 production. 83 In the same article, the authors reported the capacity of eATP to increase mRNA levels of IL-23, which potentially fosters the expansion of the proinflammatory Th17 lymphocyte subset.…”
mentioning
confidence: 99%